Genomic epidemiology of strains currently and formerly classified as Enterobacter spp. recovered from equine necropsy samples - Blandine Harel; Corinne Sévin; Simon Le Hello; Peggy Moreau; Jean-Christophe Giard; Sandrine Petry; François Gravey (PLoS ONE, 2025)
Enterobacteriaceae are opportunistic pathogens responsible for local or systemic infections in both human and veterinary medicine. To monitor circulating strains in stud farms in Normandy (France), we investigated a collection of Enterobacteriaceae isolated from necropsied equids performed in the region between 1997 and 2020. These strains were initially identified using MALDI-TOF; however, as this method failed to identify some isolates, whole genome sequencing followed by rMLST analysis was subsequently performed. Different genera were identified: Enterobacter spp., Huaxiibacter spp., Lelliottia spp., Rahnella spp.. MALDI-TOF and rMLST identifications were concordant for only 26.5% of the strains studied, leading us to conclude that rMLST is a more reliable method for both genus- and species-level identification, particularly for less-studied genera such as Huaxiibacter spp. and Rahnella spp.. The genus Enterobacter spp. ( E. hormaechei and E. ludwigii ) accounted for 53% of the strains with a high degree of sequence type (ST) diversity. These include E. hormaechei ST114 and ST171, known as high-risk clone in human clinical medicine. These clones, containing plasmids and acquired resistance genes such as blaOXA-1 , blaSHV-12 or blaTEM-1B , are resistant to at least four classes of antibiotics. The presence of genes encoding the enteroaggregative heat-stable enterotoxin 1 or the bacteriocin colicin, probably carried by plasmids, implies that Enterobacter spp. form a reservoir of antibiotic resistance and virulence factors. Conversely, strains of the genera Huaxiibacter spp., Lelliottia spp. and Rahnella spp. naturally found in the environment, showed a lean resistome and virulome. This analysis shows that genomic studies are essential to obtain precise species identification, monitor and detect high-risk clones, and to highlight the circulation of resistance and virulence genes through mobile genetic elements.